Asymmetry in college basketball players: change of direction performance in shuffle movement and 505 test - Wang, Peng; Lyu, Mengde; Geng, Na; Wu, Zirun; Ren, Xinran; Kozinc, Žiga; Kons, Rafael; Šarabon, Nejc; Miao, Xiangjun (Frontiers in Physiology, 2025)
IntroductionThis study aims to 1) examine the difference and asymmetry in change of direction in shuffle movement (CoDS) performance among basketball players; 2) assess the relationship and directional agreement between asymmetry scores of CoDS, 505, and four single leg jump tests.MethodsForty-two college basketball players performed three trials of the CoDS and 505 tests for each leg, with the fastest performance used for the final analysis. Single leg countermovement jumps, lateral jumps, broad jumps, and drop jumps were also performed for both legs. The dominant (D) limb was defined as the side that performs better, while the non-dominant (ND) limb was the opposite. Paired-sample t-tests were conducted to compare differences in D and ND across all performances. The Kappa coefficient was used to assess consistency in asymmetry direction. Spearman’s ρ correlations were applied to examine relationships between normally and non-normally distributed performance and inter-limb asymmetry data.ResultsSignificant differences were found in CoDS (Asymmetry Score = 3.66 ± 2.74, ES = 0.49, p < 0.01) and 505 (Asymmetry Score = 2.54 ± 2.28, ES = 0.34, p < 0.01) performance between D and ND limbs. However, there was no significant correlation between the asymmetry scores in CoDS and 505 (p > 0.05). The Kappa coefficients between CoDS, 505 and single leg jump tests showed poor to slight agreement (Kappa range from −0.07–0.22) regarding asymmetry direction.ConclusionThese results suggest that practitioners should specialize in assessing CoD asymmetry in both forward-backward and lateral movement performance through 505 and and CODS test.